Utilizing Parent-Child Interaction Therapy with Trauma-Directed Interaction in a Young Male in Out of Home Care Who Had Experienced Trauma. (June 2023) - Warren, Jessica M.; Hanstock, Tanya. L.; Hunt, Sally A.; Halpin, Sean A.; Warner-Metzger, Christina M.; Gurwitch, Robin
Child abuse and neglect in young children can lead to trauma-related stress symptoms that can be challenging to manage. Parent-Child Interaction Therapy (PCIT), a strong evidence-based behavioral parent training program used for young children with behavior issues, has been used in its traditional form with increasing frequency with children and families who have trauma histories, with clinicians tailoring PCIT to use with children who have experienced trauma. Trauma-Directed Interaction (TDI) is a new systematic adaption to the standard PCIT parent training program that has the potential to help treat trauma in younger children. TDI includes several trauma-informed techniques that are added to a course of standard PCIT treatment including psychoeducation regarding trauma, recognition of feelings, and emotional regulation. This case study illustrates the use of a manualized trauma adaptation to PCIT (TDI) with a three-year-old boy who had a history of child maltreatment and his caregiver. This case provides a summary of the progression of this intervention and the results obtained. Results from the case indicated that TDI treatment was effective in not only reducing child trauma and behavioral symptoms but also in reducing mild caregiver mental health concerns. The next steps for TDI treatment and need for further research are discussed.